Letter to the editor: On plurality and authorship in science. (19th May 2018) - Tang, Bor Luen
ABSTRACT: Moffatt argues that the "plurality of distinct accounts of scientific authorship" necessitates caution in attempts to identify unethical authorship practices, and urges that considerations be given to establishing a "single consensus account of authorship." The revised International Committee of Medical Journal Editors (ICMJE) criteria do capture the essential features of authorship in terms of "intellectual contribution" and "responsibility and accountability, " which would clearly demarcate academically legitimate authorship from the common misdemeanors of ghost writing and honorary authorship. However, plurality in the practice of science and credit-sharing culture at the ground would likely render universal adoption or compliance of a single consensus account of authorship untenable.